Peri-implant osteogenesis on alumina-coated titanium implants in rat femur: morphological and elemental analysis of implant surfaces - O. O. Bondarenko; A. H. Bozhko; M. A. Skoryk; N. S. Bondarenko; I. S. Shponka; O. Ye. Loskutov (Patologìâ)
Peri-implant bone tissue regeneration involves complex processes that are not yet fully understood at the cellular and molecular levels, leaving significant gaps in our knowledge that require further investigation.